Hypotension in the Right Lateral Position Secondary to Inferior Vena Cava Abnormality. Issue 6 (15th September 2015) - Hutton, Meredith J. H.; Swamy, Ganesh; Shinkaruk, Kelly; Duttchen, Kaylene
Abstract : Surgical positioning is accompanied by numerous anesthetic considerations, particularly its potential effects on the cardiovascular, respiratory, and nervous systems. Clinical studies have shown that lateral positioning does not affect hemodynamics; however, with the addition of trunk flexion, there is a decrease in cardiac output, which may be secondary to caval compression. In this report, we describe a unique case of hypotension that arose in a patient positioned only in the right lateral decubitus position with flexion and that was exacerbated by an abnormally narrow inferior vena cava.